The Distributional Impact of the Norwegian Tax Reform Measured by Disproportionality - Thor Olav Thoresen (Statistics Norway, Research Department, 1995)
This paper focuses on the measurement of progressivity and the distributional effect of the Norwegian tax reform of 1992. Progressivity is measured by the degree of disproportionality, which implies that the burden of taxes is estimated when income units are ranked according to pre-tax incomes. The measure of disproportionality is decomposed to estimate the influence from different parts of the tax system on total disproportionality. For instance, the measure of the contribution from net taxes can be decomposed into a tax base effect and a tax rate effect. The results show that the degree of progressivity in the overall tax system, as measured here, has not been altered from 1991 to 1992, but the decomposition analysis reveals that the tax base effect is more dominant and the tax rate effect is less dominant after the reform.
Keywords: D31; D33; D63; H24; 330; Tax progressivity; Income distribution; Disproportionality in the tax burden; Tax reform; Decomposition of inequality